Understanding the Chinese language a comprehensive linguistic introduction - Shei, Chris 1956- (London Routledge, 2014)
"This textbook provides a cohesive and comprehensive introduction to Chinese linguistics for all undergraduate and postgraduate students of Chinese. It covers all the main subfields of linguistics and explores in turn the sounds, vocabulary, phraseology, syntax, discourse structures and pragmatics of the Chinese language, providing students with a solid foundation with which to understand the Chinese language in a profound fashion. It also offers a free companion website"-- Provided by publisher.
Chinese sounds -- Chinese words -- Chinese sentences -- Speech acts -- Sentence final particles -- Chinese neologisms on the web.
Keywords: Chinese language -- English. -- Textbooks for foreign speakers; Chinese language -- Grammar; Chinese language -- Syntax; Chinese language -- Study and teaching -- English speakers